Smart electromechanical dustbin for dry particle / Ariff Safwan Omar, Muhammad Asyraf Mat Nawawi and Sarminadira Shaikh A.Rahim - Omar, Ariff Safwan; Mat Nawawi, Muhammad Asyraf; Shaikh A.Rahim, Sarminadira (2015)
"Smart Electromechanical Dustbin For Dry Particle" contains one (1) motor which is wiper motor, centre lock car, digital infrared and liquid crystal display (LCD) . The project is built because to upgrade in terms of versatility, security and comfort that will facilitate our daily lives. In this project, three types of circuits are combined which are power circuit (forward and reverse), voltage regulator circuit and control circuit. First, DC wiper motor can move up and down. Basic operation of this project is when digital infrared detect any particle, circuit will be trigger up and the centre lock car will lock flip flop door on dustbin and LCD will display some word to guide user when use this dustbin. After that, wiper motor will move up and down based on coding setting in PIC. At last, when the dustbin are totally full, wiper motor are not move up and down and centre lock car will lock the flip flop door and LCD will display some word to give information to user about that dustbin. Smart Electromechanical Dustbin For Dry Particle was proved can be a very useful tool in daily life.